Imaji Jembatan Lalu-Lintas: Mengunjungi Kembali Persoalan Sola Scriptura - Stephen Rehmalem Eliata (Sekolah Tinggi Teologi Intheos Surakarta, 2026)
Abstract. The doctrine of sola scriptura has been highly criticized by contemporary theologians. The critique shows that the doctrine of sola scriptura is impossible. It is based on its ontological interpretation, which is assumed to be capable of interpreting reality. This study attempts to revisit this critique. I argue that the doctrine of sola scriptura can be maintained only if it is revisited and reinterpreted. The word of God through the Bible is interpreted as the only (sola) bridge for humans to connect with God through God's visual revelation in the world. I demonstrate my argument by analyzing Calvin's thinking in his important works, namely the Institutes of the Christian Religion and A Harmony of the Gospels, and using secondary sources from contemporary Calvin scholars. My analysis indicates that, first, for Calvin, the Bible is the primary instrument of God's self-revelation to humans. Second, God reveals Himself in visible-invisible relationships through the world. Finally, the Holy Spirit works in freedom to secure God's revelation to humans.Abstrak. Ajaran mengenai sola scriptura mendapat kritik tajam dari para teolog kontemporer. Kritik tersebut menunjukkan bahwa ajaran sola scriptura adalah sebuah ketidakmungkinan. Kritik ini disebabkan oleh pemaknaannya yang bersifat ontologis yang dianggap mampu menafsir seluruh realitas. Penelitian ini mencoba mengunjungi kembali kritik tersebut. Saya berpendapat bahwa ajaran tentang sola scriptura dapat dipertahankan hanya jika dikunjungi kembali dan ditafsir ulang. Firman Allah melalui Alkitab ditafsir sebagai jembatan satu-satunya (sola) bagi manusia untuk terhubung dengan Allah melalui penyataan visual Allah dalam dunia ciptaan. Saya membuktikan pendapat dengan menganalisis pemikiran Calvin dalam karya-karya pentingnya, yaitu “Institute of Christian Religion” dan “A Harmony of the Gospels,” serta menggunakan sumber sekunder dari para peneliti kontemporer Calvin. Analisis saya menunjukkan bahwa, yang pertama, bagi Calvin Alkitab adalah instrumen primer penyataan diri Allah bagi manusia. Yang kedua, Allah menyatakan diri dalam relasi visible-invisible di dunia. Yang terakhir, Roh Kudus berkarya dalam ruang bebas untuk menjamin penyataan Allah diberikan bagi manusia.